Single-step conversion of cellulose to 5-hydroxymethylfurfural (HMF), a versatile platform chemical - Su, Yu; Brown, Heather M.; Huang, Xiwen; Zhou, Xiao-dong; Amonette, James E.; Zhang, Z. Conrad (Applied catalysis. A, General, 2009)
A new catalytic pathway is revealed for the rapid conversion of cellulose to sugars and further to 5-hydroxymethylfurfural (HMF) in a single-step process under mild temperatures (80–120 °C). Paired CuCl 2/CrCl 2 catalysts in 1-ethyl-3-methyl-imidazolium chloride solvent exhibited remarkably high activity for hydrolytic cellulose depolymerization. The product selectivity can be tuned by simply varying the CuCl 2/CrCl 2 ratio. The ability to use cellulosic biomass as feedstock for the large-scale production of liquid fuels and chemicals depends critically on the development of effective low temperature processes. One promising biomass-derived platform chemical is 5-hydroxymethylfurfural (HMF), which is suitable for alternative polymers or for liquid biofuels. While HMF can currently be made from fructose and glucose, the ability to synthesize HMF directly from raw natural cellulose would remove a major barrier to the development of a sustainable HMF platform. Here we report a single-step catalytic process where cellulose as the feed is rapidly depolymerized and the resulting glucose is converted to HMF under mild conditions. A pair of metal chlorides (CuCl 2 and CrCl 2) dissolved in 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl) at temperatures of 80–120 °C collectively catalyze the single-step process of converting cellulose to HMF with an unrefined 96% purity among recoverable products (at 55.4 ± 4.0% HMF yield). After extractive separation of HMF from the solvent, the catalytic performance of recovered [EMIM]Cl and the catalysts was maintained in repeated uses. Cellulose depolymerization occurs at a rate that is about one order of magnitude faster than conventional acid-catalyzed hydrolysis. In contrast, single metal chlorides at the same total loading showed considerably less activity under similar conditions.